EVALUASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN SUMBAWA - Muhammad Yudi Saputra; Elly Karmeli; Nining Fitriani (Samalewa: Jurnal Riset & Kajian Manajemen, 2022)
This study aims to know the performance of regional financial of Sumbawa District in 2017-2021. The type of this study was descriptive study. The data used was quantitative namely Regional Government Budget (RGB) of Sumbawa District from 2017-2021. The data used was secondary data. The methods used to collect data were through literature study. The data analysis technique was the RGB performance analysis technique which is assessed through three measures, namely the ratio of regional financial independence, the ratio of regional financial effectiveness and the ratio of regional financial efficiency. The results of the study showed that financial independence of Sumbawa in 2017-2021 was in the Very Low category with Instructive relationship pattern, then the financial effectiveness of Sumbawa District in 2017-2021 was in the Very Effective category and financial efficiency of Sumbawa District in 2017-2021 was in the Inefficient category. The Sumbawa District Government has not been able to implement regional autonomy, by reducing dependence on the central government. Therefore, it is needed the act of government to reduce dependence on external funding sources by optimizing the existing regional potential so that RGB can increase so that regional dependence on budgets from the Central and Provincial Governments can be reduced.